Photocatalytic H-2 evolution from water-methanol system by anisotropic InFeO3(ZnO)(m) oxides without cocatalyst in visible light - Narendranath, Soumya B.; Yadav, Ashok Kumar; Bhattacharyya, Dibyendu; Jha, Shambhu Nath; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2014)
InFeO3(ZnO)(m), series of oxides are found to give unprecedented H-2 evolution from water-methanol mixtures without using any cocatalysts. This family of compounds has an anisotropically layered structure in which Zn/FeOn polyhedra are sandwiched between InO6 octahedral layers. Local structure characterization by X-ray absorption spectroscopy reveals that Zn coordination changes from pentacoordinated to tetrahedral geometry across the series, whereas Fe geometry remains trigonal bipyramidal in all the compounds. This peculiar structure is conducive for a spatial separation of photogenerated charges reducing recombination losses. Band gap energies calculated from absorption spectra indicate potential visible light activity, and this may be due to the orbital mixing of Fe 3d and O 2p as revealed by pre-edge features of X-ray absorption spectra. Band positions are also advantageously placed for a visible light H-2 generation and is indeed found to be the case in methanol-assisted water splitting with standardized hydrogen evolution of similar to 19.5 mmol g(-1) h(-1) for all the catalysts.
Keywords: anisotropic structure; H-2 evolution; InFeO3(ZnO)(m); layered oxide; photocatalytic water splitting

Photocatalytic H-2 evolution from water-methanol mixtures on InGaO3(ZnO)(m) with an anisotropic layered structure modified with CuO and NiO cocatalysts - Narendranath, Soumya B.; Thekkeparambil, Saranya V.; George, Leena; Thundiyil, Shibin; Devi, R. Nandini (Journal of Molecular Catalysis A-Chemical, 2016)
InGaO3(ZnO)(m) series of oxides is found to be active for photocatalytic H-2 evolution from water-methanol mixtures. The structure of this series is highly anisotropic with InO6 octahedral layers sandwiching Ga/ZnOn polyhedra. The structural anisotropy in which the conducting layer is spatially separated from the charge generation sites may help in suppressing charge recombination and consequently enhance catalytic activity. The band gaps of the series obtained from absorption spectra are above 3.6 eV and hence they are not active under visible light irradiation. H-2 evolution is considerably enhanced under UV light on employing NiO as cocatalyst due to facile electron transfer from InGaO3(ZnO)(m). to NiO. However, when CuO is used as cocatalyst, visible light activity could be brought out. Due to the very low band gap of CuO, it can act as a sensitizer absorbing in visible light. The band positions become conducive for H-2 evolution due to band alignments consequent to electron accumulation in CuO conduction band. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: InGaO3(ZnO)(m); photocatalytic water splitting; visible light; XPS; XRD

Scalable optical fiber reactor for photocatalytic H2 production: addressing scattering issues - Walko, Priyanka S.; Devi, R. Nandini (International Journal of Hydrogen Energy, 2023)
Scattering is one of the main challenges in scaling up photocatalytic water splitting using the most prevalent powder catalysts. This can be overcome by decoupling the reaction medium from light transmission, as in the case of optical fibers. Here we explore utilizing optical fibers coated with 5 wt% CuO supported on TiO2 for photocatlytic H2 production from water-methanol mixtures. CuO/TiO2 is a well studied photo catalyst in which photoreduced Cu species are known to act as sensitizers for inducing visible light activity. Lower activity of sequentially coated systems indicates that appropriate interfaces of active Cu and TiO2 with water are desirable. The scalability of such optical fiber-based systems along with potential in non-potable turbid water media are demonstrated. Maximum activity of 22 mmoles of H2 in 8 h was obtained with 50 mg of catalyst coated on optical fibers, which increases linearly with increase in fiber numbers, whereas, drastic reduction in activity is observed in powder catalyst upon increasing the catalyst quantity. A one-to-one comparison of 700 mg of catalyst in powder form and coated on optical fibers indicates more than one order enhancement in activity in the optical fiber based system. In addition, -70% retention in activity in highly turbid non-potable water was observed as compared to powdered system which shows complete reduction in the activity by 99.99%. (c) 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CuO; Optical fibers; photocatalytic water splitting; TiO2; Total internal reflection; Visible light utilisation